2014
DOI: 10.1111/jace.12934
|View full text |Cite
|
Sign up to set email alerts
|

Pyrochlore‐Free Ferroelectric 0.64Pb(Ni1/3Nb2/3)O3–0.36PbTiO3 Ceramics Synthesized by the Combustion Method

Abstract: By adopting Nb 2 O 5 , HNO 3 and coordination agents EDTA as raw materials, pyrochlore-free 0.64Pb(Ni 1/3 Nb 2/3 )O 3 -0.36PbTiO 3 (0.64PNN-0.36PT) powders were successfully synthesized via a combustion route. Free of pyrochlore phase was realized by the chelation formation of EDTA-metal ions which isolate niobium and lead oxides and then prevent the formation of pyrochlore phases, therein generate the desired perovskite phases. Comparing the results with similar samples synthesized by the Columbite method, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Therefore, its piezoelectric and dielectric properties have been extensively investigated. [6][7][8][14][15][16][17][18] For example, Pan et al used the columbite method to synthesize PNN-PT with high d 33 (450 pC/N) around the morphotropic phase boundary (MPB). 16 Wang et al reported the dielectric properties of 0.64PNN-0.36PT ceramics, which were prepared via combustion route.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, its piezoelectric and dielectric properties have been extensively investigated. [6][7][8][14][15][16][17][18] For example, Pan et al used the columbite method to synthesize PNN-PT with high d 33 (450 pC/N) around the morphotropic phase boundary (MPB). 16 Wang et al reported the dielectric properties of 0.64PNN-0.36PT ceramics, which were prepared via combustion route.…”
Section: Introductionmentioning
confidence: 99%
“…16 Wang et al reported the dielectric properties of 0.64PNN-0.36PT ceramics, which were prepared via combustion route. 17 Piezoelectric materials at the MPB are generally known to exhibit excellent piezoelectric response. It is commonly considered that in traditional lead-based piezoelectric ceramics, the boundary of rhombohedral (R) and tetragonal (T) phases is located in the MPB, where the free energy difference between R and T phases is small, thus facilitating the alignment of domains under electric field.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these materials, special attention has been paid to perovskite-type ferroelectrics with a high piezoelectric coefficient ( d 33 ) and electromechanical coupling coefficient ( k p ) . In particular, lead-based piezoelectric ceramics such as Pb­(Zr,Ti)­O 3 and relaxor ferroelectrics represented by Pb­(Mg 1/3 Nb 2/3 )­O 3 –PbTiO 3 (PMN-PT), Pb­(Ni 1/3 Nb 2/3 )­O 3 –PbTiO 3 (PNN-PT), and Pb­(Sc 1/2 Nb 1/2 )­O 3 –PbTiO 3 (PSN-PT) are the most common binary systems with a perovskite structure. However, these classic systems fail to meet the increasing demand for the high piezoelectric performance in modern electronic devices.…”
Section: Introductionmentioning
confidence: 99%